2012
DOI: 10.1007/s10142-012-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

A candidate male-fertility female-fertility gene tagged by the soybean endogenous transposon, Tgm9

Abstract: In soybean, the W4 gene encoding dihydroflavonol-4-reductase controls anthocyanin pigment biosynthesis in flowers. The mutant allele, w4-m, is characterized by variegated flowers and was evolved from the insertion of an endogenous transposable element, Tgm9, in intron II of the W4 gene. In the w4-m mutant line, reversion of the unstable allele from variegated to normal purple flower in revertants would indicate Tgm9's excision accompanied by its insertion into a second locus. We identified a male-sterile, fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Later, Raval et al. () utilized the Tgm9 transposon tagging system to identify an insertion within a DNA/RNA helicase/DEAD‐box protein gene that caused a male‐sterile, female‐sterile mutant. Recently, it has been demonstrated that excision of the element from the gene resulted in restoration of the male and female fertility wild‐type phenotype (M.K.…”
Section: Community Accessible Soybean Mutant Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Raval et al. () utilized the Tgm9 transposon tagging system to identify an insertion within a DNA/RNA helicase/DEAD‐box protein gene that caused a male‐sterile, female‐sterile mutant. Recently, it has been demonstrated that excision of the element from the gene resulted in restoration of the male and female fertility wild‐type phenotype (M.K.…”
Section: Community Accessible Soybean Mutant Resourcesmentioning
confidence: 99%
“…This screen yielded 36 independent male-sterile, femalefertile (MSFS) mutants and 24 independent root necrotic mutants, demonstrating the ability of this transposon to mutate other genes. Later, Raval et al (2013) utilized the Tgm9 transposon tagging system to identify an insertion within a DNA/RNA helicase/DEADbox protein gene that caused a male-sterile, female-sterile mutant. Recently, it has been demonstrated that excision of the element from the gene resulted in restoration of the male and female fertility wild-type phenotype (M.K.…”
Section: Tgm9 Transposon Mutant Populationmentioning
confidence: 99%
“…This sterility gene was inherited as a single recessive nuclear gene and was nonallelic to the known male-sterile, female-sterile mutants st2, st4, st5, st6, and st7 (Palmer and Horner 2000). The st8 gene was mapped to a 62-kb region on molecular linkage group (MLG) J; the mutation was caused by the insertion of an active soybean transposable element, Tgm9 (Kato and Palmer 2003;Raval et al 2013). …”
Section: Page 3 Of 22mentioning
confidence: 99%
“…A male-sterile, female-sterile (MSFS) mutant from a germinal revertant of the w4-m line bearing purple flowers was found at Iowa State University (Raval et al 2013). The locus was mapped to molecular linkage group J (chromosome 16) through bulked segregant analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A 62-kb region was found, and fine mapping indicated that the region contained only five genes. One of the genes in that region, identified as Glyma.16G072300, encodes a helicase gene (Raval et al 2013). A rice homolog of this helicase gene has been shown to control crossing over and a sterility phenotype (Wang et al 2009).…”
Section: Introductionmentioning
confidence: 99%